Urgensi Keberadaan Perpustakaan Umum di Lhokseumawe - saiful hidayah (Universitas Syiah Kuala, 2020)
Lhokseumawe is a municipality classified into a high density of activity after Banda Aceh city. Administratively, it is noted that more than 60% of the area is used as a residential area and will continue to expand as population grows. Basically, the city of Lhokseumawe was originally a part of North Aceh district, which became the central government of North Aceh until obtained autonomy to hold its own government since 2001. Indirectly it has made the intensity of density has been solid since it was still the center of Aceh Utara district government , which is the way of life of Indonesian people in general who choose to live side by side with the busyness of a central government for the ease of reaching its public space. One public space that will receive many visits is the public library. The need for information, theory, and also the source of alloying activities. Its presence still in the government of North Aceh is located in the area of Mon Geudong, Banda Sakti, Lhokseumawe. Even though it is still located within the scope of the municipality, its reach far from the center of community activity causes the interest of citizen visiting to be less which resulted in making the library building as suspended animation. Although direct sources through gadgets are able to provide solutions, many things still have to do with visiting public libraries directly.